Preparation and Characterization of Low Polymerization Shrinkage and Bis‐GMA‐Free Dental Resin System. Issue 3 (7th January 2015) - Yuan, Shuang; Liu, Fang; He, Jingwei
ABSTRACT Because of the estrogenic effect of bisphenol A (BPA), the application of BPA derivatives such as Bis‐GMA in dentistry has been doubted. In this research, Bis‐GMA‐free dental resin systems were prepared by mixing 1, 6‐bis(2′‐methacryloyoxy‐ethoxycarbonyl‐amino)‐2, 4, 4‐trimethylhexane (UDMA), silicon containing dimethacrylate monomer (SiMA), and triethyleneglycol dimethacrylate (TEGDMA) together with different mass fraction. Double bond conversion, polymerization shrinkage, flexural strength, flexural, water sorption, and water solubility of prepared resins were investigated. Results showed that when UDMA/SiMA/TEGDMA was present in the ratio of 9:1:10 (wt/wt/wt), the obtained resin had the best comprehensive physicochemical properties and potential to be used as Bis‐GMA‐free dental resin.